2018
DOI: 10.1038/s41598-018-31014-3
|View full text |Cite
|
Sign up to set email alerts
|

4D imaging reveals stage dependent random and directed cell motion during somite morphogenesis

Abstract: Somites are paired embryonic segments that form in a regular sequence from unsegmented mesoderm during vertebrate development. Although transient structures they are of fundamental importance as they generate cell lineages of the musculoskeletal system in the trunk such as cartilage, tendon, bone, endothelial cells and skeletal muscle. Surprisingly, very little is known about cellular dynamics underlying the morphological transitions during somite differentiation. Here, we address this by examining cellular re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As the body axis extends, it consecutively generates pairs of somites 3 epithelial spheres comprised of multipotent progenitor cells. In response to extrinsic signals, epithelial somites (ES) undergo dramatic morphogenetic changes and reorganise 4 7 . On the ventral side cells undergo an epithelial to mesenchymal transition (EMT) to form the sclerotome, while on the dorsal side the cells in the dermomyotome remain epithelial.…”
Section: Introductionmentioning
confidence: 99%
“…As the body axis extends, it consecutively generates pairs of somites 3 epithelial spheres comprised of multipotent progenitor cells. In response to extrinsic signals, epithelial somites (ES) undergo dramatic morphogenetic changes and reorganise 4 7 . On the ventral side cells undergo an epithelial to mesenchymal transition (EMT) to form the sclerotome, while on the dorsal side the cells in the dermomyotome remain epithelial.…”
Section: Introductionmentioning
confidence: 99%
“…During the development of somatic segments, sarcomeres originate mainly from the directional migration of precursor cells in the dermomyotome and then fuse into mature muscle fibers. 37 , 38 , 39 , 40 Sufficient quantities of myoblasts and their normal migration function are needed to ensure precise directional migration during somatic segmental development. 41 , 42 Otherwise, impaired myoblasts might lead to an asymmetric distribution of epaxial muscle and eventually result in the morphological and functional imbalance of paravertebral muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking of GFP-labelled cells showed that the dorsal dermomyotome produces the myotome layer in multiple waves, with the first myocytes specified adjacent to the neural tube (Gros et al, 2004). Live-imaging of cellular rearrangements examined the morphological transformations of somites from epithelial structures to somites with a mesenchymal sclerotome, located ventrally, and an epaxial myotome abutting the neural tube (McColl et al, 2018). This uncovered differential cell sizes and regions of proliferation as well as a directed movement of dermomyotomal progenitor cells towards the rostro-medial domain of the dermomyotome, where skeletal muscle formation initiates.…”
Section: Introductionmentioning
confidence: 99%